1995
DOI: 10.1002/j.1460-2075.1995.tb07249.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of an SH2-containing protein tyrosine phosphatase is coupled to platelet thrombin receptor via a pertussis toxin-sensitive heterotrimeric G-protein.

Abstract: Corresponding author SH-PTP1 is a protein tyrosine phosphatase (PTP) predominantly expressed in haematopoietic cells and containing two src homology-2 (SH2) domains. Here we report that SH-PTP1 is phosphorylated on both serine and tyrosine residues in response to thrombin or phorbol myristate acetate (PMA), which increased by 60 and 40%, respectively, SH-PTP1 activity. Thrombin-induced phosphorylation of SH-PTP1 is an early signalling event (maximal within 10 s) involving neither integrin signalling, nor calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 76 publications
4
60
1
Order By: Relevance
“…In the present report, we showed that PTP1C was phosphorylated on tyrosine after platelet activation [23,24], thereby forming a binding site to the c-Src SH2 domain.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…In the present report, we showed that PTP1C was phosphorylated on tyrosine after platelet activation [23,24], thereby forming a binding site to the c-Src SH2 domain.…”
Section: Discussionmentioning
confidence: 48%
“…A Cell lysate ti ~n [23,24]. The migration in SDS-PAGE of PTP1C corresponded to the migration of the prominent tyrosine protein of 64 kDa [29].…”
Section: Tl Falet Et Al/febs Letters 383 (1996) 165-169mentioning
confidence: 99%
See 3 more Smart Citations